2009
DOI: 10.1093/gerona/gln041
|View full text |Cite
|
Sign up to set email alerts
|

The Lifestyle Interventions and Independence for Elders Pilot (LIFE-P): 2-Year Follow-up

Abstract: Older adults who have compromised physical function are able to sustain some of the benefits derived from participating in structured PA 2 years after supervised treatment has been terminated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 15 publications
3
75
0
2
Order By: Relevance
“…Is associated with Frailty ↓ IGF-1, ↓ DHEAS, ↓ free testosterone [77] IGF insulin-like growth factor, DHEAS dehydroepiandrosterone sulfate hormones is clear, and there is also a decrease in dehydroepiandrosterone (sulfate), growth hormone and IGF-1 [69]. Abnormal hormone levels in women are also associated with frailty (Table 4).…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Is associated with Frailty ↓ IGF-1, ↓ DHEAS, ↓ free testosterone [77] IGF insulin-like growth factor, DHEAS dehydroepiandrosterone sulfate hormones is clear, and there is also a decrease in dehydroepiandrosterone (sulfate), growth hormone and IGF-1 [69]. Abnormal hormone levels in women are also associated with frailty (Table 4).…”
Section: Pathophysiologymentioning
confidence: 99%
“…A real-life primary outcome, even if improvements in surrogates are achieved, should be based on dependency. The ongoing lifestyle interventions and independence for elders study (The LIFE study), a multicenter Phase III trial of physical activity or health education in 1,600 high-risk sedentary older persons, has operationalized the primary outcome of major mobility disability as the inability to perform the 400-meter walk [77,78].…”
Section: The Way Aheadmentioning
confidence: 99%
“…Despite the limited number of studies comparing the effects of strength training, endurance training, and concurrent training interventions on functional test performance, it is important to highlight the positive effect of concurrent training on the functional capacity of elderly populations (Binder et al 2004;Pahor et al 2006;Rejeski et al 2009;Izquierdo et al 2012). In the study by Rejeski et al (2009), 2 years of combined endurance and strength training resulted in an improved 400-m walking speed and physical performance battery that included balance, 4 m of selfpaced walking speed, and chair stands.…”
Section: Long-term Concurrent Training Programsmentioning
confidence: 99%
“…In the study by Rejeski et al (2009), 2 years of combined endurance and strength training resulted in an improved 400-m walking speed and physical performance battery that included balance, 4 m of selfpaced walking speed, and chair stands. In another study, Binder et al (2004) demonstrated enhanced scores in an assessment of muscle strength, gait, balance, body composition, and quality of life after 5 years of a physical therapy program that was composed of strength and endurance training in elderly men and women who had experienced surgical repair of a proximal femur fracture.…”
Section: Long-term Concurrent Training Programsmentioning
confidence: 99%
“…This might suggest that in older individuals regular physical activity may provide physiological improvements which in turn reduce "the rate of aging" [25]. A number of reports from large epidemiological studies have shown that increasing habitual physical activity prevents the decline in mobility-related physical performance in older adults [26][27][28][29][30][31]. These studies assessed habitual physical activity using subjective reports (i.e., questionnaires) [32].…”
Section: Introductionmentioning
confidence: 99%